2018
DOI: 10.21041/ra.v9i1.213
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of reinforced concrete beams strengthened with steel bars and epoxy structural adhesive

Abstract: This work was aimed at analyzing the efficiency of the strengthening of reinforced concrete beams with the addition of steel bars and epoxy adhesive. Five beams were produced, out of which four beams were strengthened to flexure. In two of them, “U” clips were also used to improve the anchorage of the strengthening. The tests demonstrated that the clips reduced the resistances of the beams compared to those without clips. The strengthened beams without clips yielded better results, but the largest limiting fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…In [4], the authors reported a similar study with the use of CFRP sheets. Authors in [9] found that beams with openings located at the mid-span failed due to shear, which was unexpected. On the other hand, beams with openings located at the support failed due to flexural failure without any significant impact on the ultimate load [9].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In [4], the authors reported a similar study with the use of CFRP sheets. Authors in [9] found that beams with openings located at the mid-span failed due to shear, which was unexpected. On the other hand, beams with openings located at the support failed due to flexural failure without any significant impact on the ultimate load [9].…”
Section: Introductionmentioning
confidence: 96%
“…Authors in [9] found that beams with openings located at the mid-span failed due to shear, which was unexpected. On the other hand, beams with openings located at the support failed due to flexural failure without any significant impact on the ultimate load [9]. It was reported that beams with openings reinforced with a steel sleeve exhibit higher bearing capacity and lower deformation capabilities compared to circular beams without reinforcement [10].…”
Section: Introductionmentioning
confidence: 96%